2016
DOI: 10.1038/srep35078
|View full text |Cite
|
Sign up to set email alerts
|

Airy beam self-focusing in a photorefractive medium

Abstract: The unique bending and shape-preserving properties of optical Airy beams offer a large range of applications in for example beam routing, optical waveguiding, particle manipulation and plasmonics. In these applications and others, the Airy beam may experience nonlinear light-matter interactions which in turn modify the Airy beam properties and propagation. A well-known example is light self-focusing that leads to the formation of spatial soliton. Here, we unveil experimentally the self-focusing properties of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 20 publications
(31 reference statements)
1
15
0
1
Order By: Relevance
“…While a weak focusing or a defocusing nonlinearity enable the Airy beam to self-trap and to preserve the Airy properties over a larger distance 6 , it has been demonstrated that a strong focusing nonlinearity leads to a break-down of the Airy beam into what has been called an off-shooting soliton (OSS) and a remaining accelerating structure 7 9 . Recently we have experimentally demonstrated the self-focusing properties of a 1D-Airy beam in a nonlinear photorefractive crystal 10 and confirm the true solitonic property of the resulting OSS 11 .…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…While a weak focusing or a defocusing nonlinearity enable the Airy beam to self-trap and to preserve the Airy properties over a larger distance 6 , it has been demonstrated that a strong focusing nonlinearity leads to a break-down of the Airy beam into what has been called an off-shooting soliton (OSS) and a remaining accelerating structure 7 9 . Recently we have experimentally demonstrated the self-focusing properties of a 1D-Airy beam in a nonlinear photorefractive crystal 10 and confirm the true solitonic property of the resulting OSS 11 .…”
Section: Introductionsupporting
confidence: 57%
“…As detailed in ref. 10 , a single propagating Airy beam under strong nonlinear focusing condition turns into a solitonic beam (off-shooting soliton or OSS) at the transverse zero-deflection position [ A 1 0 in Fig. 2(a) ], that coexists with an accelerating beam structure [ A 1 1 at z = L in Fig.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…where F 0 (respectively B 0 ) is the wave amplitude, Ai is the Airy function, a the truncation parameter of the Airy beam. To simulate the behavior of the propagation of the antisymmetric Airy beams, we use the same theoretical model as in [10,11,[22][23][24]. The nonlinear propagation of the two incoherent counter-propagating beams can be expressed as follows:…”
Section: Antisymmetric Airy Beams Interactions Schemementioning
confidence: 99%
“…This self-healing, shape-preserving, accelerating beam has multiple applications from manipulating microparticles [3] and plasma channel generation [4] to all-optical routing [5], or light-sheet microscopy [6]. Recently, the self trapping character of Airy beams in biased nonlinear media has suggested interesting dynamics such as soliton-like behaviors [7][8][9][10][11]. Co-propagating Airy beams and their interactions have been studied in different medias ranging from nematic liquid crystals [12] to photonic lattices [13] or threewave systems [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation